Enhanced defluoridation in household filter using binary metal hydrochar composite. (10th October 2022) - Yadav, Krishna; Prabhakar, Roshan; Jagadevan, Sheeja
Abstract: Elevated fluoride concentration in water can trigger several health-related problems. In this study, the influence of post pyrolysis hydrothermal activation on defluoridation has been investigated to check their interacting effect using response surface methodology. Amongst the various optimizing factors which were investigated, temperature and time emerged as the most significant factors ( p -value < 0.05). The Fe–Zn (2:1) binary metal hydrochar composite synthesized from optimized hydrochar demonstrated an optimum dose, contact time, initial concentration and solution pH of 0.8 g/L, 120 min, 5 mg/L and 7 respectively. The isotherm and kinetic results indicated that experimental data best fitted to Langmuir and pseudo-second order, with a determination coefficient approaching one (R 2  = 0.99). Maximum monolayer adsorption capacity for this composite was found to be 28.41 mg/g. Thermodynamic parameters corroborate that defluoridation was chemisorption in nature (ΔH⁰ >10 kJ/mol) and was favoured at lower temperature (30 °C). An extensive characterization was employed to explain the adsorption mechanism, and confirmed occurrence of Lewis acid-base interactions, ion-exchange processes and electrostatic interactions. The performance of a fixed bed column was assessed based on breakthrough curve analysis. This novel composite could therefore serve as an efficient fluoride adsorbent because of enhanced sorption at neutral pH and reusability, thereby ensuring a sustainable and practical solution for low-cost defluoridation of drinking water. Graphical abstract: Image 1 Highlights: Hydrolytic temperature and time were significant factors affecting defluoridation. Optimized hydrochar was selected as feed material for composite synthesis. Synergistic effect of binary metal hydrochar composite was investigated. Fluoride adsorption was driven by an electrostatic and ion-exchange mechanism. Adsorbent effectiveness for defluoridation was tested as a potential filter media.